O Departamento Municipal de Cultura de São Paulo (1935-1938): políticas de criação de bibliotecas e democratização de leitura - Gomes, Denise Pedroso (2008)
The present work, of historical nature, analyzes the public politics libraries creation of the Municipal Culture Department of São Paulo in 1935 -1938. In this period Mário de Andrade was in front of this Department and he instituted the public libraries expansion program in São Paulo city. The objective of the Culture Department was not only to increase the cultural goods generation, but do them get around, what explains the proposal of popular libraries creation that should work as a service in order to guide the people in your readings and like this, to contribute for the disclosure of the reading habit. Considering then, the importance of the public libraries in the reading democratization, this study tries to understand as the public politics of libraries creation they compose repertoires and prescribe reading practices from the collections formation and it searches to understand the representation of reading democratization that the public libraries expansion program of the Municipal Culture Department sustained in the delimited period, as well as the representation that possessed of reader's formation. This research also search to understand as the Infantile Library it was constituted in the space of practices and the reading rituals idealized by the Culture Department, at least concerning the reading representations for the childhood and for the youth